Quellen und Bäche mit Blockgletschereinfluss - Lösch, B.; Tolotti, M.; Alber, R. (country:IT, 2015)
For this project running waters with and without influence of rockglaciers were studied. Various chemical and physical parameters, benthic fauna and diatoms were analysed. Running waters influenced by rockglaciers present low water temperature, high conductivity levels, high concentrations of sulphate, magnesium and calcium and often also high levels of metals. Diversity and abundance of aquatic organisms (macro and meiobenthic fauna and diatoms) in the stretches of water affected by rockglaciers are clearly lower than in reference stretches of water unaffected by them. The macrobenthical fauna in running waters influenced by rockglaciers is very similar to the fauna of running waters fed by glaciers. The most common taxa are larvae of chironomids of the subfamilies of Diamesinae and Orthocladiinae. The high levels of metals represente a clear limiting factor for the macrozoobenthos. In most of the running waters analysed oligotraphentic diatoms dominate. Despite the high concentration of heavy metals no teratological forms were found. Apart from the chemical factors also the geographical position of the sampling points influences the differences in the diatom species composition.